KAJIAN KEPUASAN PEMUSTAKA LAYANAN PESAN ANTAR SILAKAN DALAM MASA PANDEMI COVID-19 DI PERPUSTAKAAN PROKLAMATOR BUNG KARNO - Ide Yohane (Perpustakaan Nasional RI, 2022)
Perpustakaan Proklamator Bung Karno has made a new innovation in book lending service during Covid-19 pandemic. The innovation is a book delivery order system called Silakan. User can access library collections optimally and safely with Silakan. Moreover, it can reduce the risk of Covid-19 transmission and spread in the library. The aim of this research is to find out the level of satisfaction in using Silakan delivery order service and to be evaluation tool for public services during Covid-19 pandemic. The methodology of this research is qualitative. The uses are really appreciate and give positive response to Silakan delivery order service. Based on survey of Silakan delivery order service, the user satisfaction index is 3,765 (scale 4). The result is that the quality of Silakan delivery order service is category A, which means that the perception of its performance is very good.